On the analysis of a passive vibration absorber for submerged beams under hydrodynamic forces: An optimal design. (1st October 2020) - Abdollahi, Ali; Khadem, S.E.; Khazaee, Mostafa; Moslemi, Amin
Highlights: Vibro-impact NES is applied for passive vibration control of beams. Numerical and analytical approaches are employed to analyze the system. Various response regimes are observed in the dynamic of the system. The optimal design and parameter study are also performed. The SMR and Two impacts per cycle regime are the best responses. Abstract: This paper investigates the passive vibration control of immersed beams under sinusoidal hydrodynamic forces using a vibro-impact nonlinear energy sink (VI-NES). This type of absorber has a lower activation threshold compared to other nonlinear isolators. It is comprised of a clearance containing an impact element. Neither spring nor damper is required, and the restitution coefficient is the only source of damping. The equation of motion of the coupled system is analytically solved utilizing the multiple scales method and is verified via a numerical solution. The strongly modulated response (SMR), chaotic response, regimes with two impacts per cycle (symmetric and asymmetric) and more than two impacts per cycle have been observed in the nonlinear dynamic behavior of the coupled system which is associated with the location of the fixed points on the slow invariant manifold (SIM). The optimal design of the absorber is also investigated for the impulsive excitation case. Here, it is aimed to decrease the amount of time that takes the absorber to mitigate 95 percent of the primary system's initial energy. The absorber location, restitution coefficient, clearance length, and mass ratio between the impact element and the beam are treated as design parameters. Furthermore, the influence of the design parameters on the SIM and the transient dynamic behavior of the system is also studied. The results show that the optimally designed absorber can mitigate the initial energy of the structure in a short time. It is observed that the strongly modulated response and the regime with two impacts per cycle (symmetric) are the most optimal responses. Also, comparing the performance of the mentioned absorber to the cubic NES yields satisfying results.